Development of a practical sandwich assay to detect human pluripotent stem cells using cell culture media - Hiroaki Tateno; Keiko Hiemori; Kazunari Hirayasu; Nagako Sougawa; Masakazu Fukuda; Masaki Warashina; Makoto Amano; Taku Funakoshi; Yoshifusa Sadamura; Shigeru Miyagawa; Atsuhiro Saito; Yoshiki Sawa; et al. (Regenerative Therapy, 2017)
Human pluripotent stem cells are considered to be ideal cell sources for regenerative medicine, but their clinical and industrial application is hindered by their tumorigenic potential. Previously we have identified a pluripotent stem cell-specific lectin rBC2LCN recognizing podocalyxin as a cell surface ligand. More recently, podocalyxin was found to be a soluble ligand of rBC2LCN that is secreted specifically from human pluripotent stem cells into cell culture media. Taking advantage of this phenomenon, we have previously developed a sandwich assay targeting the soluble podocalyxin using rBC2LCN as a capturing probe and another lectin rABA as an overlay probe to detect human pluripotent stem cells residing in cell therapy products derived from human pluripotent stem cells. A drawback to this, however, was that cell culture media containing fetal bovine serum was found to cause a substantial background signal to the sandwich assay. To reduce the background and increase the sensitivity, we screened different overlay probes to detect the soluble podocalyxin. Among them, an anti-keratan sulfate monoclonal antibody called R-10G showed the highest sensitivity and provided a low background signal to fetal bovine serum. The established sandwich assay using rBC2LCN and R-10G was proved to be powerful, which allowed the high-sensitive detection of human induced pluripotent stem cells residing among clinical-grade cardiomyocytes and neural stem cells, both derived from human induced pluripotent stem cells. The developed method has a possibility to be a standard technology to detect human induced pluripotent stem cells resided in various types of cell therapy products.